2023
DOI: 10.1002/wps.21056
|View full text |Cite
|
Sign up to set email alerts
|

The future of psychopharmacology: a critical appraisal of ongoing phase 2/3 trials, and of some current trends aiming to de‐risk trial programmes of novel agents

Abstract: Despite considerable progress in pharmacotherapy over the past seven decades, many mental disorders remain insufficiently treated. This situation is in part due to the limited knowledge of the pathophysiology of these disorders and the lack of biological markers to stratify and individualize patient selection, but also to a still restricted number of mechanisms of action being targeted in monotherapy or combination/augmentation treatment, as well as to a variety of challenges threatening the successful develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
48
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 243 publications
(274 reference statements)
0
48
0
Order By: Relevance
“…The excellent review of current efforts and issues in the field of psychopharmacology produced by Correll et al 1 does not, unfortunately, provide much that would convince skeptical decision makers that the fu-ture of psychopharmacology will look that much different from the past. I write from the perspective of selection of compounds and mechanisms for clinical devel opment as well as of implementation of clinical stud-ies across phases 1-3, both from the industry and the US National Institute of Mental Health (NIMH) vantage points.…”
Section: Real Changes Can Enhance Information Yield On Novel Psychoph...mentioning
confidence: 99%
See 1 more Smart Citation
“…The excellent review of current efforts and issues in the field of psychopharmacology produced by Correll et al 1 does not, unfortunately, provide much that would convince skeptical decision makers that the fu-ture of psychopharmacology will look that much different from the past. I write from the perspective of selection of compounds and mechanisms for clinical devel opment as well as of implementation of clinical stud-ies across phases 1-3, both from the industry and the US National Institute of Mental Health (NIMH) vantage points.…”
Section: Real Changes Can Enhance Information Yield On Novel Psychoph...mentioning
confidence: 99%
“…The thoughtful review by Correll et al 1 ex­plores the status of drugs for mental disorders with new mechanisms of action cur­rently in testing, and details obstacles to developing such medications. The authors examined established clinical registries and identified ongoing clinical trials of agents that showed the most promise “as emerging from documented superiority over placebo, magnitude of the observed effects, and dem­onstration of requirements for safety and tol­erability”.…”
mentioning
confidence: 99%
“…Correll et al 1 correctly state that many psychiatric disorders remain insufficiently treated despite advances in psychopharmacology, and attribute this to the limited knowledge of pathophysiology of these disorders, the lack of biological markers precluding tailored treatment selection, the few mechanistic targets for treatment development, and the challenges with clinical trial design and conduct. Here I address the chasms at the various levels of the translational spectrum that should be targeted through innovations in order to advance psychopharmacology and improve outcomes for patients.…”
mentioning
confidence: 99%
“…The excellent review of current efforts and issues in the field of psychopharmacology produced by Correll et al 1 does not, unfortunately, provide much that would convince skeptical decision makers that the future of psychopharmacology will look that much different from the past. I write from the perspective of selection of compounds and mechanisms for clinical devel­opment as well as of implementation of clinical stud­ies across phases 1‐3, both from the industry and the US National Institute of Mental Health (NIMH) vantage points.…”
mentioning
confidence: 99%